Socialization of Green Bean Juice (Phaseolus Radiates) in Increasing Hemoglobin Levels in Postpartum Mothers with Anemia At Pratama Cahaya Clinic - Ika Nur Saputri; Nurianti, Irma; Hariati, Mayang Citra; Nasution, Lisyah Syaharani (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2024)
The postpartum period is a critical period for the life of the mother and the newborn baby, which can often result in death. Intensive care is always needed to avoid the dangers of complications. If the postpartum mother experiences anemia, the hemoglobin level will be less than 11 gr / dl. In order for postpartum mothers to avoid anemia, it is recommended to consume at least 90 iron tablets. Green beans generally contain 6.7 mg of iron in 100 grams. This socialization activity aims to increase the knowledge of PkM participants in implementing the right actions when postpartum mothers experience anemia. The process of consuming green bean juice is also relatively practical for postpartum mothers so that it is easy to prepare. Community service activities in the form of providing material in the form of socialization, where before and after the socialization, pre and post-tests will be given to measure the increase in knowledge. PkM participants numbered 20 postpartum mothers at the Pratama Cahaya clinic. The average pre-test score for PkM participants was 57.5 or categorized as less good and there was an increase after the post-test to 74.5 which was categorized as good. It can be seen that there was an increase in knowledge of 17.0. This socialization succeeded in increasing participants' knowledge regarding the benefits of green bean juice, the process of preparing green bean juice to be served, and the impact on pregnant women if Hb levels are low during the postpartum period.